TEACHING COLLOCATION USING LEXICAL APPROACH AS USED IN MADE FRIDA YULIA’S VOCABULARY: LEXICALLY-BASED SECOND THOUSANDS WORDS OF GENERAL SERVICE LIST BOOK - Petrus Chandra (JURNAL SOSIAL HUMANIORA (JSH), 2014)
This research was to give insight to English teachers and practitioners who had the same problem faced by the writer and his students especially dealing with the lack of collocation. Moreover, this research inspired particularly those who involved in teaching practices for how to improve their professionalism by implementing Lexical-Based Approach in class activities and to find the solution and hindrances for a better teaching technique in the future. For students who had problems in collocation, this Lexical-Based Approach as used in Made Frida Yulia’s Vocabulary: Lexically-Based Second Thousand Words of General Service List book might improve the awareness toward lexical phrases, chunks and collocations. For teachers and practitioners who want to use this Lexical-Based Approach in the future could use bilingual explanation that is needed for Indonesian students rather than monolingual explanation in English, try to create a good note taking habit for lexical phrases as soon as possible, and use vivid pictures or audio visuals to kill the boredom of the students.